Swings and Roundabouts : a Self-Coaching Workbook for Parents and Those Considering Becoming Parents - Golawski, Anna (Professional coaching series., 2013)
This coaching workbook is the result of a collaboration between the University of East London and two parent-coaches. The authors are themselves parents who have been on a journey of ""swings and roundabouts""--Experienced the highs and lows of having children. Having difficulties knowing how to parent in many situations, which was not made easier by the conflicting advice in the media, made them unsure of their own parenting skills. This was one of the reasons that they entered into the field of parent-coaching. They were trained coaches who wanted to use their coaching skills and experienc